Spatial and Temporal Planetary Boundary Layer Moisture‐Source Variability of Crimean Peninsula Precipitation - Langhamer, Lukas; Dublyansky, Yuri; Schneider, Christoph; Dublyansky, Yuri; 2 University of Innsbruck Institute of Geology Innsbruck Austria; Schneider, Christoph; 1 Humboldt‐Universität zu Berlin Department of Geography Berlin Germany (Earth and Space Science, 2021)
The atmospheric water cycle is a key component of the global energy and moisture exchange. In order to gain better understanding of the atmospheric processes and temporal variability and trends affecting precipitation in Crimea, we use a Lagrangian moisture source detection technique based on reanalysis data from the European Center for Medium‐Range Weather Forecasts. The study presents a quantitative picture of the major moisture sources that feed precipitation on the Crimean peninsula from February 1979 to January 2017. In total 51.3% of moisture stems from marine sources. Specifically, the main individual contributors are the Mediterranean Sea (15.3%), the Black Sea (14.4%), and the North Atlantic Ocean (13.9%). Continental moisture recycling contributes additional 46.9%. The amounts of moisture contribution from marine and continental sources and their respective moisture transport pathways are subject to strong seasonality. Winter precipitation in Crimea is predominantly sourced by the Mediterranean Sea. Long‐term temporal trends in contribution from any of the major moisture sources are absent during the study period. Statistically significant negative correlation between the North Atlantic Oscillation (NAO) index and contribution from moisture sources exists in winter for the Mediterranean (R = −0.22) and Black Seas (R = −0.23), and for the southern continental moisture source (R = −0.37). The North Atlantic Ocean moisture source exhibits a statistically significant positive correlation with NAO index during spring (R = 0.32). Plain Language Summary: The atmospheric water cycle is a component of the global water cycle. It describes the behavior of water in the atmosphere from the evaporation in the source region to the final precipitation. This study presents a comprehensive picture of the precipitation water sources for the Crimean peninsula from 1979 to 2017. Additionally, trajectories allow to estimate travel times and pathways of air parcels. Approximately half of the Crimean precipitation ...